TINJAUAN KELENGKAPAN REKAM MEDIS PADA FORMULIR LAPORAN OPERASI DI RUMAH SAKIT SUMBER WARAS KABUPATEN CIREBON - Nirma Alfiani; Dede Setiawan; Sumarni (LPPM ITEKES Mahardika, 2020)
Medical records as evidence of health services have an important role in proving law including forms on medical records that have specific functions and meanings in each item. One of which is an operating report that is the contents of an everlasting or perpetuated medical record. The purpose of this research is to know a deeper overview of the completeness of the medical record on the Operation report form at the Sumber Waras Hospital of Cirebon Regency. The type of research used is descriptive research. Data collection techniques using an observation method with the research instrument sheet Checklist. Simple random sampling techniques. The sample in this study is the medical record of the operating patients in the Cirebon district source Waras Hospital as much as 72 medical record documents. The results of the medical record in the Operations report form there are 11 documents (15%) a fully stocked and 61 documents (85%.) that are not fully stocked. The conclusion obtained in this study is that the minimum medical record service standard at Sumber Waras Hospital in Cirebon Regency is not in accordance with Kepmenkes number 129 of 2008.